The impact of hybrid working models on work-life balance: A mediation analysis among female IT professionals in the National Capital Region, India - Sharma, Nidhi; Mishra, Nishith Kumar (The International tax journal, 2026)
The COVID-19 pandemic led to widespread adoption of hybrid working models which resulted in significant changes to workplace dynamics. The researchers employ three mediation analysis methods to study how hybrid work systems impact work-life balance (WLB) of female IT workers in India's National Capital Region (NCR). Our research uses Baron and Kenny's (1986) causal steps method to analyze survey data from 120 female IT professionals for testing four hypotheses about direct and mediated effects between variables. The research demonstrates that hybrid work setups benefit WLB (β=0.72, p<0.001) through two processes which include reduced workplace challenges (indirect effect=0.23, Sobel z=4.2, p<0.001) and increased organizational support (indirect effect=0.29, Sobel z=5.1, p<0.001). The communication problems create a negative effect on the advantages (β=-0.52, p<0.001) which organizations provide their employees because they create support that increases work performance (β=0.48, p<0.001). The research results validate flexibility stigma theory and Conservation of Resources framework by providing HR policy recommendations that help organizations achieve gender equity in hybrid work environments. The practical applications focus on three areas which include technology infrastructure development, mental health support systems, and performance evaluation frameworks that promote inclusivity for teams working in different locations.